A conversation on the effects of the COVID-19 pandemic on junior researchers’ careers with funders and university leaders (Nature Portfolio, 2021)
The various restrictions applied across the globe to contain the COVID-19 pandemic have been impacting the way we knew how to work. Dr. Matthews (a scientific program manager at the National Institute of Neurological Disorders and Stroke—NINDS), Dr. David del Álamo Rodriguez (head of the European Molecular Biology Organization—EMBO—fellowship program), and Dr. Gray (Associate Dean for the Sciences at the Advanced Science Research Center of the City University of New York) shared with Nature Communications their thoughts on how funders and university leadership can support early career researchers and young faculty through the COVID-19 pandemic.